Chronic Opioid Use Is Associated With Surgical Site Infection After Lumbar Fusion. Issue 12 (15th June 2020) - Pirkle, Sean; Reddy, Srikanth; Bhattacharjee, Sarah; Shi, Lewis L.; Lee, Michael J.
Abstract : Study Design: Retrospective, database review. Objective: The purpose of this study was to explore the association between preoperative opioid use and postoperative infection requiring operative wound washout in elective lumbar fusion patients. Summary of Background Data: Numerous peer-reviewed publications have conducted multivariate analyses of risk factors for surgical site infection. However, few have explored preoperative opioid use. Opioids have been widely prescribed preoperatively for pain management, but their effect on postsurgical infection is currently inconclusive. Methods: We retrospectively queried the PearlDiver national insurance claims database and included patients from 2007 to 2017 with a history of lumbar fusion. Any interbody fusion history designated exclusion. We stratified patients by single or multilevel procedures and conducted univariate analyses of previously documented infection risk factors, as well as our variable of interest, chronic preoperative opioid use. Variables associated ( P < 0.100) with the outcome measure of 90-day postoperative infection treated with operative irrigation and wound debridement were included in a multivariate analysis. Results: A total of 12, 519 patients matched our inclusion criteria. Among the single-level cohort, only diabetes was observed to be associated with infection requiring operative wound washout and thus no subsequent regression was performed. For the cohort of patients who underwent multilevel fusion, chronic opioid use, diabetes, congestive heart failure, chronic obstructive pulmonary disease, and hypertension trended toward significance in the univariate analysis and were included in a logistic regression model. In the multivariate analysis, chronic opioid use (odds ratio [OR] = 1.435, P = 0.025), diabetes (OR = 1.591 P = 0.003), and congestive heart failure (OR = 1.929, P = 0.003) were identified as independent risk factors for infection requiring operative wound washout. Conclusion: In this analysis, preoperative opioid use was significantly associated with infection requiring operative wound washout in multilevel lumbar fusion patients. Limiting opioid consumption may have the benefit of reducing the risk of infection following spine surgery. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textPrescription opioids are widely utilized in the management of chronic pain; therefore, understanding a possible relationship between its consumption and postoperative complications is of great importance. In this study, we report that a chronic preoperative opioid regimen is significantly associated with surgical site infection requiring irrigation and wound debridement.